Justification to all: liberalism, legitimacy, and theology - Billingham, P (2015)
This thesis concerns the reason-giving aspect of legitimacy. What reasons must be used to justify coercive laws, if citizens are to be respected as morally free and equal, in the face of their many moral, religious, and philosophical disagreements? Many theorists endorse 'political liberalism', according to which laws must be justified to all citizens by reasons that they can accept. This claim has been interpreted in two conflicting ways. The dominant view, which I call 'public reason liberalism', holds that laws must be justified by appeal to a set of values that all citizens can share, despite their many disagreements. In the first part of the thesis, I argue that this view should be rejected in favour of 'justificatory liberalism', which holds that laws must be conclusively justified to each citizen on the basis of all of their reasons. I also respond to the challenge of the 'right reasons view', which rejects the claim that laws need to be justified to citizens by reasons they can accept. Several prominent objections to political liberalism claim that it is incompatible with committed religious belief. In the second part of the thesis I investigate whether this is the case with regard to Christianity, by engaging with Christian theology. I argue that many of the common objections to political liberalism fail, but so do certain arguments that aim to show that Christians ought to endorse public reason liberalism on the basis of their religious beliefs. Nonetheless, Christians can accept political liberalism, and justificatory liberalism in particular. The requirements of justificatory liberalism and individuals' Christian beliefs will sometimes conflict, however. Justificatory liberals should accept that individuals can sometimes justifiably prioritise the latter over the former. My overall argument is that justificatory liberalism offers the best account of the reason-giving aspect of legitimacy, and that this is partly shown by its compatibility with Christian theology.